2007
DOI: 10.1016/j.jsbmb.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of acquired resistance to endocrine therapy in hormone-dependent breast cancer cells

Abstract: Acquired resistance is a major problem limiting the clinical benefit of endocrine therapy. To investigate the mechanisms involved, two in vitro models were developed from MCF-7 cells. Long-term culture of MCF-7 cells in estrogen deprived medium (LTED) mimics aromatase inhibition in patients. Continued exposure of MCF-7 to tamoxifen represents a model of acquired resistance to antiestrogens (TAM-R). Long-term estrogen deprivation results in sustained activation of the ERK MAP kinase and the PI3 kinase/mTOR path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 43 publications
3
57
0
4
Order By: Relevance
“…Other TamR sublines derived in our laboratories were shown to have constitutive activation of Akt (Frogne et al, 2005) and increased level of PKCd (Nabha et al, 2005) and PKCa (Frankel et al, 2007). Other groups have reported that activation of several growth factor receptor pathways, including ERBB2, EGFR and PKA can lead to Tam resistance (Shou et al, 2004;Yue et al, 2007;Pancholi et al, 2008). Interestingly, we could demonstrate Tab2-dependency also in BT474 cells, which carry amplified HER2.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Other TamR sublines derived in our laboratories were shown to have constitutive activation of Akt (Frogne et al, 2005) and increased level of PKCd (Nabha et al, 2005) and PKCa (Frankel et al, 2007). Other groups have reported that activation of several growth factor receptor pathways, including ERBB2, EGFR and PKA can lead to Tam resistance (Shou et al, 2004;Yue et al, 2007;Pancholi et al, 2008). Interestingly, we could demonstrate Tab2-dependency also in BT474 cells, which carry amplified HER2.…”
Section: Discussionsupporting
confidence: 59%
“…Among the mechanisms proposed to explain primary and acquired Tam resistance in breast cancer cells that maintain expression of ERa, there are constitutive activation of components of signaling pathways stemming from membrane growth factor receptors, resulting in re-distribution of coactivators or corepressors (Privalsky, 2004;Frogne et al, 2005;Schiff et al, 2005;Frankel et al, 2007;Yue et al, 2007;Pancholi et al, 2008;Musgrove and Sutherland, 2009). In addition, it was shown that the coactivator SRC3/AIB1, which is often amplified and overexpressed in breast cancer, induced Tam resistance in vitro (Osborne et al, 2003), in a similar way as it did a decreased level of NCoR corepressor (Lavinsky et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the same Src modulations occur with antiestrogen therapies. Elevated Src levels have been shown to be associated with tamoxifen resistance, and treatment with a Src inhibitor prevented or reversed the development of this resistance (53,54). Two phase II studies are exploring the combination of these antiestrogen agents and Src inhibitors in randomized trials in breast cancer.…”
Section: Thetransition Of Src Inhibitors To the Clinicmentioning
confidence: 99%
“…Indeed, it has been demonstrated that the expression of a constitutively active c-Src attenuated the sensitivity of MCF7 breast cancer cells to tamoxifen (Morgan et al, 2009). In the same cell line the synergistic interaction between ER, EGF receptor and c-Src enhanced tumour cell responsiveness to mitogenic stimuli, allowing their survival also in the presence of tamoxifen (Yue et al, 2007).…”
Section: C-src As Pharmacological Target In Bone Metastasesmentioning
confidence: 98%